SCAPE: gap analysis on action services tools and SCAPE platform and testbeds requirements - Ferreira, Miguel (2013)
This document presents a gap analysis on the current state of development of preservation components in SCAPE against the SCAPE Platform and the Testbed scenarios. In this analysis, the functionality of existing preservation components is compared to SCAPE Testbed scenario requirements and published as a Gap Analysis, which will serve as the basis for tool development in the Preservation Components Sub-project during the next phase of the project.